Developing a Qur’anic Competency Framework for Pesantren Educators through Tafsir Tarbawi - Ade Nurhayat; Elis Tuti Winaningsih (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
Research on pesantren educators has primarily focused on teaching practices, kyai leadership, and character education, while studies developing a competency framework grounded in Qur’anic educational values remain limited. This study aims to develop a Qur’anic competency framework for pesantren educators through the synthesis of thematic Qur’anic interpretation and educational competency theory. The study employed a qualitative conceptual research approach using a library research design. The primary data consisted of six groups of Qur’anic educational verses, purposively selected based on their relevance to the core educational roles of pesantren educators, including religious instruction, character formation, leadership, communication, spiritual development, and lifelong learning. Secondary data were obtained from classical and contemporary Qur’anic exegesis, Islamic education literature, and scholarly publications on teacher competency and pesantren education. Data were analyzed through the stages of identifying Qur’anic educational values, conceptual synthesis, and competency framework development. The findings propose six competency domains for pesantren educators: spiritual, academic, pedagogical, leadership, communication, and professional development competencies. The study proposes the Qur’anic Competency Framework for Pesantren Educators (QCF-PE) as a conceptual framework, positioning spiritual competency as the core competency integrating all other domains. The proposed framework contributes theoretically to the development of tafsir tarbawi studies while providing a conceptual foundation for future competency development and empirical validation in Islamic boarding schools.